Voluntary Minimum Wages: The Local Labor Market Effects of National Retailer Policies - Derenoncourt, Ellora; Weil, David (Quarterly Journal of Economics, 2025)
ABSTRACT Low unionization rates, a falling real federal minimum wage, and outsourcing have hampered wage growth in the low-wage sector in the United States for several decades. In recent years (2014–2023), a number of large private retailers—including some of the largest employers in the United States—have opted to institute or raise company-wide, voluntary minimum wages (VMWs) for their employees. We use anonymized payroll data from a large credit bureau and a major payroll provider to study the effects of these national retailer policies on adopting employers’ own wages and employment as well as their spillovers to other employers in shared local labor markets, variously defined. Using stacked event studies centered around multiple VMW events and a continuous treatment variable defined as the gap between local-area wages and the company minimum, we find that VMWs result in sizable wage increases and reductions in turnover at the companies that implement them. Turning to wages at other companies, we estimate small, often economically negligible, spillover effects across multiple measures of exposure to VMWs and numerous definitions of relevant competitors, including firms connected by worker flows. Together, the evidence points to little role for strategic interactions in the transmission of large retailers’ wage policies to other firms. Voluntary minimum wage policies have affected over 3 million jobs at adopting employers, yet their impact on the broader labor market is limited.